The craft-a-day book : 30 projects to make with recycled materials - Cornell, Kari A. (Twenty-First Century Books, 2018)
Provides thirty craft projects using recycled materials from around the house. Includes color photographs, step-by-step instructions, sidebars to encourage further embellishment, a list of craft resource books, and websites for further information.